Longevity of Daphnia and the attenuation of stress responses by melatonin - Schwarzenberger, Anke (BMC Physiol, 2014)
BACKGROUND: The widespread occurrence of melatonin in prokaryotes as well as eukaryotes indicates that this indoleamine is considerably old. This high evolutionary age has led to the development of diverse functions of melatonin in different organisms, such as the detoxification of reactive oxygen species and anti-stress effects. In insects, i.e. Drosophila, the addition of melatonin has also been shown to increase the life span of this arthropod, probably by reducing age-related increasing oxidative stress. Although the presence of melatonin was recently found to exist in the ecological and toxicological model organism Daphnia, its function in this cladoceran has thus far not been addressed. Therefore, we challenged Daphnia with three different stressors in order to investigate potential stress-response attenuating effects of melatonin. i) Female and male daphnids were exposed to melatonin in a longevity experiment, ii) Daphnia were confronted with stress signals from the invertebrate predator Chaoborus sp., and iii) Daphnia were grown in high densities, i.e. under crowding-stress conditions. RESULTS: In our experiments we were able to show that longevity of daphnids was not affected by melatonin. Therefore, age-related increasing oxidative stress was probably not compensated by added melatonin. However, melatonin significantly attenuated Daphnia’s response to acute predator stress, i.e. the formation of neckteeth which decrease the ability of the gape-limited predator Chaoborus sp. to handle their prey. In addition, melatonin decreased the extent of crowding-related production of resting eggs of Daphnia. CONCLUSIONS: Our results confirm the effect of melatonin on inhibition of stress-signal responses of Daphnia. Until now, only a single study demonstrated melatonin effects on behavioral responses due to vertebrate kairomones, whereas we clearly show a more general effect of melatonin: i) on morphological predator defense induced by an invertebrate kairomone and ii) on life history characteristics transmitted by chemical cues from conspecifics. Therefore, we could generally confirm that melatonin plays a role in the attenuation of responses to different stressors in Daphnia.